Opinião dos alunos quanto ao ensino dos diagnósticos de enfermagem segundo a taxonomia da NANDA Students opinion as to the eaching of the nursing diagnosis according to NANDA - Maria Helena Baena de Moraes Lopes; Ianê Nogueira do Vale; Margarida Barbosa (SciELO, 1997)
Acreditando na importância do diagnóstico de enfermagem,o seu ensino foi introduzido ha 4 anos nas disciplinas de Assistência de Enfermagem à Saúde da mulher e Enfermagem Perinatal, no 6o. período do curso de graduação em enfermagem da UNICAMP. Com o intuito de avaliar essa experiência, propusémo-nos a levantar a opinião dos alunos e obter subsídios para aprimorar o ensino. Foram ministradas 4 horas de ensino teórico e indicada bibliografia básica. A aplicação prática supervisionada foi desenvolvida durante 21 horas numa unidade neonatal e 45 horas em centros de saúde. Ao término das disciplinas, 16 alunos responderam a um questionário com questões fechadas e abertas. O grupo de alunos respondentes foi unânime em considerar válido o estudo dos diagnósticos de enfermagem. A maioria considerou mais adequado introduzir o ensino no 3o. semestre, quando se iniciam os procedimentos básicos de enfermagem. Quanto à dificuldade de aprendizado do uso dos diagnósticos, 68, 7% dos alunos relataram um nível de dificuldade superior a 25% e inferior a 75%. O grupo de alunos como um todo achou que o estudo do diagnóstico de enfermagem trouxe modificações no seu conceito de assistência de enfermagem. In accordance to North American Nursing Diagnosis Association (NANDA) , nursing diagnosis is a clinical judgement of the individual, family or community answers to the vital process or to the actual or potential health problems.These gives the basis for the itervention selection, by which the nurse is responsible. Believing in the importance of nursing diagnosis, its teaching was introduced 4 years ago In the subjects of Womans Health Assistence and Perinatal Nursing, In the 6o. period of the undergraduate course In nursing at UNICAMP. Aiming At evaluating these experience, we proposed to get the students opinion and obtain subsides to perfect teaching. Teoric teaching of 4 hours was given and it was indicated the basical bibliography. The supervised pratical application was developed during 21 hours in a neonatal unit and 45 hours in health, centers. At the end of the subjects, 16 students aswered a form with closed and open questions. All the students considered valid the study of the nursing diagnoses. Most of the students considered more proper to introduce the teaching in the 3°. semester, when the nursing basic procedues is begun. As to the difficult of learning in the use of diagnoses, 68,7% of the students reported a diffucult level higher to 25% and lower to 75%. The students group consideres that the study of nursing diagnoses brought modifications in, its concept of nursing assistance.